The Effect Of Love Of Money And Situational Pressure On Fraud With Self Control As A Moderating Variable - Maxwell Gilbert Malaihollo; Christina Sososutiksno; Paul Usmany (LP2M IAIN Palopo, 2025)
This study aims to determine the influence of love of money and situational pressure on deprivation, with self-control as a moderating variable. This study used a quantitative approach with a survey method through the distribution of questionnaires to purposively selected respondents. The sample in this study consisted of 40 respondents in 20 regional government agencies (OPD) of the Maluku Provincial Government. Data analysis used multiple linear regression analysis and moderated regression analysis (MRA). Based on the results of multiple linear regression tests and moderation analysis in this study, a deep understanding was obtained regarding the relationship between the variables of love of money , situational pressure, self-control , and fraudulent acts in ASN in the Maluku Provincial Government. Partially, the love of money variable showed an insignificant effect on fraudulent acts, with a regression coefficient of -0.133 and a significance value of 0.244 (p > 0.05). Meanwhile, the results of testing the situational pressure variable showed a significant effect on fraudulent acts, with a regression coefficient of -0.441 and a significance value of 0.026 (p < 0.05). Furthermore, testing the role of self-control as a moderating variable showed that self-control significantly moderated the relationship between love of money and fraudulent acts, but did not significantly moderate the relationship between situational pressure and fraudulent acts. The interaction coefficient value between love of money and self-control was -0.243 with a significance value of 0.004, indicating that self-control was able to weaken the negative influence of love of money on fraudulent acts.